Rare presentations of Acute Acquired Demyelinating Syndromes (ADS) among children - Joy, Jeffy; Xavier, Rose; Jose, Ebin; Varghese, Binoj (Nepal Journal of Neuroscience, 2024)
Acute demyelinating syndromes (ADS) in children presents with neurological symptoms with a pathology involving either single central nervous system (CNS) location (mono focal ADS) or multiple sites (poly focal ADS), with or without encephalopathy. It is a diagnostic dilemma requiring a high index of suspicion. A thorough clinical examination with neuroimaging and cerebrospinal fluid (CSF) analysis is needed for making a diagnosis. Clear cut guidelines regarding long term management and prognosis is lacking. Myelin oligodendrocyte glycoprotein (MOG) antibody must be done in all suspected cases as it helps in prognosticating and counselling parents. Recurrence is rare, recovery is usually complete and most children respond to pulse high dose methylprednisolone injection. In this case series we map out different unique presentations of acute ADS with and without Myelin oligodendrocyte glycoprotein (MOG) antibody positivity among children from a tertiary care hospital in central Kerala, India.